Evaluation of reproductive performance of beef heifers mated at 14, 18 and 26 months of age - Gottschall, Carlos Santos (2007)
The objective of this study was to evaluate the reproductive performance of heifers mated at 14, 18 and 26 months of age. The study was based on data collected from 2003 to 2005 from 270 heifers (Aberdeen Angus, Devon and cross-breeds) and mated at 14 (A14, n = 70), 18 (A18, n = 36) and 26 months old (A26, n = 164). The attributes analyzed among the different groups were age at mating (AM), average weight gain from birth to mating (AWG-BM), weight at mating (WM) and pregnancy rate (PR). The PR was tested using Qui-square test and the average weight gains and weight at mating were tested using the test t of Student. The WM was 312.0 kg for the A14 group, 333.0 kg for the A18 and 297.4 kg for the A26 group, where the A18 was different than A14 and A26 (P < 0.01). The AWG-BM was 0.658 kg, 0.507 kg and 0.353 kg for the A14, A18 and A26 groups, respectively, showing significance differences (P < 0.01). The PR was 84.3% for the A14 group, 94.4% for the A18 and 90.9% for the A26 animals group (P > 0.05). Thus, it is possible to conclude that the different ages at mating did not influence on the pregnancy rate.